The Labour Market Impact of the COVID-19 Pandemic on Individuals with Disabilities: The Case of Ireland - Elish Kelly; Bertrand Maitre (Institute of Labor Economics (IZA), 2025)
The COVID-19 health pandemic had a profound impact on labour markets worldwide, disproportionately affecting subgroups of the population, including individuals with disabilities. Despite extensive research on the broader impacts of the pandemic, there remains a notable gap in the literature concerning the labour market impact of COVID-19 on people with disabilities. This paper attempts to fill this gap for Ireland by examining the impact of the pandemic on disabled peoples' unemployment status. The paper finds that individuals with disabilities were 2.7 percentage points more likely to be unemployed during the pandemic compared to those without disabilities. Even in 2023, people with disabilities remained more likely to be unemployed. However, our year interaction models revealed that the impact of disabilities on unemployment risk remained largely stable during and after the pandemic.
Keywords: J01; J14; J18; J64; J68; 330; COVID-19; disabilities; unemployment risk; Ireland; OLS